The potential role of Th17 lymphocytes in patients with psoriasis - Mahnaz Mansouri; Parvine Mansouri; Abbas Ali Raze; Zohreh Jadali (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Background: Psoriasis is a chronic inflammatory disorder, characterized by increased keratinocyte proliferation due to abnormal differentiation of basal keratinocytes. The etiology of the disease is unclear, and according to the survey results, it is hypothesized that a combination of genetic and environmental factors prompts an abnormal immune response in patients with psoriasis. CD4+ Th cells play a multifaceted role in both immune defense and pathogenesis of certain diseases such as psoriasis. Nonetheless, the exact contribution of different subpopulations of Th cells in psoriasis is still not clear. Objective: The aim of present study was to determine the mRNA expression level of RORC as potential inducer of Th17 cell differentiation and expression pattern of Th17-signature cytokines (IL-17A and IL-22). Methods: Twenty patients with psoriasis and twenty-one healthy subjects were included in the study. Peripheral blood mononuclear cells (PBMCs) were separated and expression of three genes were determined by quantitative real-time reverse transcriptase PCR (qRT-PCR). Plasma levels of IL-17 and IL-22 were also evaluated by ELISA. Results: RORC, IL-17A and IL-22 gene expression was significantly higher in patients with psoriasis compared with healthy controls (P<0.05). In addition, a marked increase in plasma IL-17A and IL-22 levels was observed in patient group compared to controls (P<0.001). Study limitations: small number of patients. Conclusion: These data suggest that Th17 response may contribute to the pathogenesis of psoriasis.